Enhanced microwave absorption property of reduced graphene oxide (RGO)-strontium hexaferrite (SF)/poly (vinylidene) fluoride (PVDF) - Acharya, Sanghamitra; Gopinath, Chinnakonda S.; Alegaonkar, Prashant; Datar, Suwarna (Dimond and Related Materials, 2018)
Enormous growth in the use of electronic gadgets presents a challenge to develop efficient electromagnetic interference (EMI) shielding materials specifically using composites with properties such as light weight and high shielding due to absorption. In the present work we have synthesized a composite material with three components; Reduced Graphene Oxide (RGO) and Strontium Hexaferrite (SrFe12O19) (SF) bound together by polymer Poly (Vinylidene) Fluoride (PVDF). Composite RGO/SF (RGOSF) was prepared by facile one port chemical reduction method. Surface anchoring of similar to 500 nm of magnetic particles over the graphene sheet was confirmed by Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). Crystal structure of SF particles was analyzed before and after composite formation with RGO. Effective crystallite size was estimated from both XRD and Raman Spectroscopy which showed similar trend moving from SF to RGOSF to RGOSFPVDF. Polymer composite films of RGOSFPVDF were prepared by hot pressing. Both real and imaginary part of magnetic and dielectric parameters were studied. It was observed that enhancement of interfacial polarization and anisotropic heat loss in PVDF matrix was generated by RGOSF which ultimately created more scattering center and helped in absorption of electromagnetic radiation. Critical film thickness of 3 mm was capable to shield up to 33 dB EM energy of which > 99.9% was due to absorption.

Investigation of disorder in mixed phase, sp(2)-sp(3) bonded graphene-like nanocarbon - Patil, Sumati; Kolekar, Sadhu; Kumar, Arvind; Alegaonkar, Prashant; Datar, Suwarna; Dharmadhikari, C. V. (Journal of Nanoscience and Nanotechnology, 2018)
Disorder in a mixed phase, sp(2)-sp(3) bonded graphene-like nanocarbon (GNC) lattice has been extensively studied for its electronic and field emission properties. Morphological investigations are performed using scanning electron microscopy (SEM) which depicts microstructures comprising of atomically flat terraces (c-planes) with an abundance of edges (ab planes which are orthogonal to c-planes). Scanning tunneling microscopy (STM) is used to observe the atomic structure of basal planes whereas field emission microscopy (FEM) is found to be suitable for resolving nanotopography of edges. STM images revealed the hexagonal and non-hexagonal atomic arrangements in addition to a variety of defect structures. Scanning tunneling spectroscopy is carried out to study the effect of this short-range disorder on the local density of states. Current versus voltage (I-V) characteristics have been recorded at different defect sites and are compared with respect to the extent of the defect. As sharp edges of GNC are expected to be excellent field emitters, because of low work function and high electric field, enhancement in current is observed particularly when applied electric field is along basal planes. Therefore, it is worthwhile to investigate field emission from these samples. The FEM images show a cluster of bright spots at low voltages which later transformed into an array resembling ledges of ab-planes with increasing voltage. Reproducible I-V curves yield linear Fowler-Nordheim plots supporting field emission as the dominant mechanism of electron emission. Turn on field for 10 mu A current is estimated to be similar to 3 V/mu m.
Keywords: Field emission microscopy; Graphene-Like Nanocarbon; Scanning tunneling microscopy; Scanning Tunneling Spectroscopy